Electroconvulsive Therapy for Neuropsychiatric Symptoms due to Major Neurocognitive Disorder: A Prospective, Observational Study. Issue 2 (June 2022) - Chan, Peter; Waxman, Robyn E.; Woo, Simon; Docherty, Claire; Rayani, Kaveh; Fischler, Ilan; Ghaffar, Omar; Elmi, Sarah
Abstract : Objectives: Neuropsychiatric symptoms (NPSs) in those with major neurocognitive disorder (MNCD) include the responsive behaviors of agitation and aggression. Electroconvulsive therapy (ECT) has shown some effectiveness based on retrospective studies and one open label prospective study. We hypothesized that ECT will reduce NPSs between baseline and after treatment in those with medication-refractory behaviors. Method/Design: This Canadian prospective multicenter study included MNCD patients admitted to geriatric psychiatry units for the management of refractory NPSs. All treatment-refractory participants suffered from advanced MNCD. We conducted the Neuropsychiatric Inventory—Clinician version and the Pittsburgh Agitation Scale at baseline, and during and after the ECT course. A bitemporal or bifrontal ECT series based on dose titration to 1.5 to 2.5 times seizure threshold was administered. Results: Data were collected for 33 patients with a mean age of 73 and categorized with severe MNCD using the Functional Assessment Staging of Alzheimer's Disease scale (stages 6 and 7). The data showed a drop in mean Neuropsychiatric Inventory—Clinician version from 58.36 to 24.58 ( P < 0.0001). Mean Neuropsychiatric Inventory agitation subscale dropped from 7.12 to 3.09 ( P = 0.007). Mean Neuropsychiatric Inventory aggression subscale dropped from 6.94 to 0.97 ( P < 0.0001). There was a concomitant significant decline in Pittsburgh Agitation Scale scores. No participants dropped out because of intolerance of ECT. One participant died from pneumonia, which did not appear related to ECT. Conclusions: In this naturalistic study, ECT was found to be a safe and effective treatment for certain NPSs in people with MNCD. This can translate into improving quality of life.